TheDeveloperBlog.com

Home | Contact Us

C-Sharp | Java | Python | Swift | GO | WPF | Ruby | Scala | F# | JavaScript | SQL | PHP | Angular | HTML

DBMS Inference Rule

DBMS Inference Rule with DBMS Overview, DBMS vs Files System, DBMS Architecture, Three schema Architecture, DBMS Language, DBMS Keys, DBMS Generalization, DBMS Specialization, Relational Model concept, SQL Introduction, Advantage of SQL, DBMS Normalization, Functional Dependency, DBMS Schedule, Concurrency Control etc.

<< Back to DBMS

Inference Rule (IR):

  • The Armstrong's axioms are the basic inference rule.
  • Armstrong's axioms are used to conclude functional dependencies on a relational database.
  • The inference rule is a type of assertion. It can apply to a set of FD(functional dependency) to derive other FD.
  • Using the inference rule, we can derive additional functional dependency from the initial set.

The Functional dependency has 6 types of inference rule:

1. Reflexive Rule (IR1)

In the reflexive rule, if Y is a subset of X, then X determines Y.

    If X ⊇ Y then X  →    Y

Example:

X = {a, b, c, d, e}
Y = {a, b, c}

2. Augmentation Rule (IR2)

The augmentation is also called as a partial dependency. In augmentation, if X determines Y, then XZ determines YZ for any Z.

If X    →  Y then XZ   →   YZ 

Example:

For R(ABCD),  if A   →   B then AC  →   BC

3. Transitive Rule (IR3)

In the transitive rule, if X determines Y and Y determine Z, then X must also determine Z.

If X   →   Y and Y  →  Z then X  →   Z  

4. Union Rule (IR4)

Union rule says, if X determines Y and X determines Z, then X must also determine Y and Z.

If X    →  Y and X   →  Z then X  →    YZ   

Proof:

1. X → Y (given)
2. X → Z (given)
3. X → XY (using IR2 on 1 by augmentation with X. Where XX = X)
4. XY → YZ (using IR2 on 2 by augmentation with Y)
5. X → YZ (using IR3 on 3 and 4)

5. Decomposition Rule (IR5)

Decomposition rule is also known as project rule. It is the reverse of union rule.

This Rule says, if X determines Y and Z, then X determines Y and X determines Z separately.

If X   →   YZ then X   →   Y and X  →    Z 

Proof:

1. X → YZ (given)
2. YZ → Y (using IR1 Rule)
3. X → Y (using IR3 on 1 and 2)

6. Pseudo transitive Rule (IR6)

In Pseudo transitive Rule, if X determines Y and YZ determines W, then XZ determines W.

If X   →   Y and YZ   →   W then XZ   →   W 

Proof:

1. X → Y (given)
2. WY → Z (given)
3. WX → WY (using IR2 on 1 by augmenting with W)
4. WX → Z (using IR3 on 3 and 2)

Next TopicDBMS Normalization




Related Links:


Related Links

Adjectives Ado Ai Android Angular Antonyms Apache Articles Asp Autocad Automata Aws Azure Basic Binary Bitcoin Blockchain C Cassandra Change Coa Computer Control Cpp Create Creating C-Sharp Cyber Daa Data Dbms Deletion Devops Difference Discrete Es6 Ethical Examples Features Firebase Flutter Fs Git Go Hbase History Hive Hiveql How Html Idioms Insertion Installing Ios Java Joomla Js Kafka Kali Laravel Logical Machine Matlab Matrix Mongodb Mysql One Opencv Oracle Ordering Os Pandas Php Pig Pl Postgresql Powershell Prepositions Program Python React Ruby Scala Selecting Selenium Sentence Seo Sharepoint Software Spellings Spotting Spring Sql Sqlite Sqoop Svn Swift Synonyms Talend Testng Types Uml Unity Vbnet Verbal Webdriver What Wpf